Diagnostic accuracy of cytology for canine osteosarcoma compared to histopathology - Oikonomidis, Ioannis; Tsouloufi, Theodora (Veterinary Evidence, 2021)
PICO question What is the sensitivity and specificity of cytology as a test for canine osteosarcoma when compared to histopathology as a gold standard? Clinical bottom line Category of research question Diagnosis The number and type of study designs reviewed Overall, four diagnostic validity studies (two prospective and two retrospective) were critically appraised Strength of evidence Weak to moderate Outcomes reported There is evidence of moderate strength to support that cytology is highly sensitive and specific for diagnosing histologically confirmed osteosarcomas as mesenchymal malignant neoplasms (cytological diagnosis of sarcoma). Evidence of weak strength suggests that the sensitivity and specificity of cytology for identifying the exact histotype (cytological diagnosis of osteosarcoma) are low and high, respectively. Finally, there is currently evidence of weak strength indicating that the sensitivity and specificity of cytology are comparable to that of preoperative histopathology after incisional biopsy for the diagnosis of canine osteosarcoma Conclusion Based on the available evidence, the diagnostic accuracy of cytology in diagnosing histologically confirmed osteosarcomas as sarcomas is high, whereas a confident conclusion cannot be drawn regarding the diagnostic accuracy of cytology for the identification of the exact histotype (cytological diagnosis of osteosarcoma). There is currently scant evidence suggesting that cytology has comparable diagnostic accuracy to preoperative histopathology (i.e. after incisional biopsy) for the diagnosis of canine osteosarcomas, however, more studies are warranted to confirm these results How to apply this evidence in practice The application of evidence into practice should take into account multiple factors, not limited to: individual clinical expertise, patient’s circumstances and owners’ values, country, location or clinic where you work, the individual case in front of you, the availability of therapies and resources. Knowledge Summaries are a resource to help reinforce or inform decision making. They do not override the responsibility or judgement of the practitioner to do what is best for the animal in their care.